The Influence of Discount, Electronic Word of Mouth (e-WOM), and Perceived Ease of Use on Purchase Decision of TikTok GO Users in Surabaya - Putra, Farrel Apta Kassuma; Rusdianto, R. Yuniardi (Academia Open, 2026)
General Background The digital economy’s rapid growth has significantly transformed consumer behavior, with social commerce platforms becoming essential channels for information seeking and online transactions. Specific Background TikTok GO has emerged as a prominent social commerce ecosystem, integrating promotional content, interactive user engagement, and streamlined transaction systems for a massive user base in Indonesia. Knowledge Gap While social commerce adoption is widespread, empirical evidence specifically analyzing how price incentives, social interaction, and platform usability converge to drive purchase decisions within the TikTok GO environment in Surabaya remains insufficient. Aims This study investigates the extent to which discounts, electronic word of mouth (e-WOM), and perceived ease of use drive purchase decisions among TikTok GO users in Surabaya. Results Quantitative analysis of 160 respondents using multiple linear regression demonstrates that discounts, e-WOM, and perceived ease of use are key determinants, with each factor exerting a positive and statistically significant contribution to buying behavior. Collectively, these variables explain 55.4% of the variance in consumer decisions. Novelty This research integrates pricing, social influence, and technological usability into a unified model, providing a comprehensive assessment of the multifaceted drivers behind social commerce transactions. Implications These findings provide managers with a strategic foundation to optimize promotional tactics and platform usability, thereby strengthening consumer engagement and increasing conversion rates in competitive digital marketplaces. Highlights: Discount strategies represent the most dominant driver of consumer purchasing behavior in social commerce. Electronic word of mouth serves as a critical mechanism for establishing consumer trust and reducing evaluation uncertainty. Perceived ease of use acts as an essential facilitator that lowers friction during the digital transaction process. Keywords: Discount, Electronic Word Of Mouth, Perceived Ease Of Use, Purchase Decision, TikTok GO